A SYSTEMATIC LITERATURE REVIEW ON INSTITUTIONAL THEORY (2020-2025) - Maslanna Ridha Siregar; Sambas Ade Kesuma (RADJA PUBLIKA, 2025)
This systematic literature review explores how institutional theory has been applied in research on organizations and management between 2020 and 2025. Its primary objective is to identify key themes, theoretical perspectives, research methods, and gaps in the recent institutional literature. The research process followed the PRISMA protocol, analyzing 20 Scopus-indexed journal articles. The results indicate that research has evolved from traditional approaches such as legitimacy and isomorphism to concepts such as institutional logics, institutional work, and integration with sustainability and human resource management studies. Methodologically, qualitative case studies and quantitative cross-sectional studies predominate, while conceptual articles and systematic reviews also play a significant role. Key gaps identified include a lack of longitudinal research, a limited focus on developing countries, and limited exploration of micro-level institutional processes. The study concludes with recommendations for future research directions to make institutional theory more relevant to the challenges of modern organizations.